2020
DOI: 10.29019/enfoqueute.v11n4.602
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and microbial group behavior of postharvest peruvian cocoa bean (Theobroma cacao L.)

Abstract: Cocoa is used in the manufacturing of different products. Fermenting microorganisms such as yeast and bacteria use the high nutrient content of cocoa. This research evaluated physicochemical properties and microbial group behavior of fresh cocoa bean and four treatments to compare among them (A, A-farmer, B, and B-farmer). Moisture content, mold and yeast count, and Salmonella were determined in fresh cocoa beans and treatments. The results of fresh cocoa beans were moisture content of 56.30 ± 0.02 % and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…The fat percentage of CNFA beans were similar in all samples, with values between 45.2 and 54.4%. These results are similar to those reported by various authors (Calvo et al, 2021;Grassia et al, 2019;Salazar et al, 2020). However, values lower than 52% of fat in cocoa are considered low, since a normal value is registered between 52 and 55% (Grassia et al, 2019;Salazar et al, 2020).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The fat percentage of CNFA beans were similar in all samples, with values between 45.2 and 54.4%. These results are similar to those reported by various authors (Calvo et al, 2021;Grassia et al, 2019;Salazar et al, 2020). However, values lower than 52% of fat in cocoa are considered low, since a normal value is registered between 52 and 55% (Grassia et al, 2019;Salazar et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…These results are similar to those reported by various authors (Calvo et al, 2021;Grassia et al, 2019;Salazar et al, 2020). However, values lower than 52% of fat in cocoa are considered low, since a normal value is registered between 52 and 55% (Grassia et al, 2019;Salazar et al, 2020). The low-fat percentage values in the CNFA beans may be related to the fermentation time, since Afoakwa et al (2013) and Aremu et al (1995) reported that the fat content in cocoa beans is related to the greater number of days of fermentation.…”
Section: Resultssupporting
confidence: 90%
“…Salazar et al [122] conducted observations of microbiological properties in postharvest handling of cocoa beans, where 4 types of treatment were carried out, namely, treatment A and A-farmer, treatment B and B-farmer. Treatments A and A-farmer (performed by farmers directly in the field) were carried out by drying cocoa beans through an artificial process, while treatments B and B-farmers (carried out by farmers directly in the field) were performed using sunlight.…”
Section: Dryingmentioning
confidence: 99%
“…The highest TAM and yeast values were also found in the fresh samples because cocoa beans in the pods were still sterile after being cut. The moisture and high sugar content in fresh cocoa beans were used for the growth and development of microorganisms [7,122].…”
Section: Dryingmentioning
confidence: 99%
See 1 more Smart Citation